Slang Language in the Subtitle of “The Social Network” Movie - Kevin Sienatra (Institute of Research and Community Outreach - Petra Christian University, 2021)
Movies are everyday entertainment for people in their daily lives. There are a lot of foreign movies that are being played in Indonesian theatres. Unfortunately, there are many places where people watch the movie with the subtitles that are not created by the professional translators. The Social Network was translated by more than one translator. This research was conducted to analyze how accurate the translation is and what the similarities and differences between the translators are. This study is a qualitative descriptive study, which analyzes the slang word translation accuracy in the movie The Social Network using Newmark theories of translation quality assessment. The finding of the study showed that the translation from both of the translators is accurate enough and there is almost no inaccurate translation, also there are several slang words that are not included in the data of the previous study, but the writer found on subtitle the data of the other two translators. Keywords: Slang, Translation, Accuracy